Novel treatment by Roux-en-Y duodenojejunostomy for perforated duodenum diverticulum - Šileikis, Audrius; Šileikytė, Auksė (Lietuvos chirurgija, 2017)
Duodenum diverticulum is the most common site for diverticular disease of small intestine. Symptomatic duodenal diverticulum are 1% to 5%, which present with pain, bleeding, inflammation, cholestasis, cholangitis, obstruction, perforation, pancreatitis, or malignant transformation. The most difficult complication is perforation – 0.03%. Once duodenal diverticulitis perforation has been diagnosed, traditional management has been simple diverticulectomy and two layer closure of the duodenum with drainage of the retroperitoneum. However, nowadays there is increase in case reports of successful conservative and different surgical treatment. We present our experience by treating duodenal diverticulitis with simple diversion by Roux-en-Y duodenojejunostomy according to Shigeru Fujisaki after unsuccessful conservative treatment.